Cybernetic Communication: Exploring the Role of AI as an Empathic Human Listener - Mohd Hanafi Jumrah; Aisah Hossin (Journal of English Language Teaching and Applied Linguistics, 2026)
Background: The emergence of artificial intelligence (AI) has transformed the landscape of human life, particularly in the way emotional expression is mediated. Humans have discovered new channels for emotional engagement through interactions with AI.  Aims: This study explores the phenomenon of emotional cybernetic communication, focusing on how individuals interact with AI systems such as ChatGPT as empathic conversational agents.  Methods: A qualitative research design was adopted, using in-depth semi-structured interviews with 28 active AI Chabot users in Malaysia, selected through purposive sampling. At the data analysis stage, the qualitative software ATLAS.ti was used to conduct thematic analysis following the procedures outlined by Braun & Clarke. Result: The study employs Parasocial Interaction Theory, focusing on three dimensions: (i) One-way relationships, (ii) Simulative intimacy, and (iii) Emotional involvement and trust. The findings reveal that participants perceive AI as a non-judgmental, emotionally responsive, psychologically safe space to express their thoughts and feelings. Three main themes emerged: (i) Emotional intimacy with AI, (ii) Empathic trust in AI, and (iii) The therapeutic value of interaction without human social pressure.  Conclusion: This study shows that parasocial interactions between humans and AI Chabot’s constitute a unique and complex emotional experience. This study contributes to the growing discourse on human-AI communication by highlighting the evolving role of AI not merely as an informational tool but as an emotionally engaged talker. The implications extend to digital mental health support, the ethics of machine empathy, and design of future human-AI interactions.